Packet sniffer and analyzer / Zarina Mohamed Alias - Zarina, Mohamed Alias (2005)
With the proliferation of the Intranet, there is a vast amount of digital information stored in the file server and shared within an organization, It is extremely difficult to monitor all access and action on a network. With numerous incidents these days, the fact that a company cannot monitor all the actions on their network can contribute to a serious problem. Packet sniffer and analyzer, also known as network protocol analyzer is a stand alone system used to monitor network. It has the capability of filtering network traffic based on Internet Protocol (IP) address, port number and protocols. It behaves as a useful tool for network administrators, network engineer and network. Hacker use packet sniffer to obtain usernames, passwords, credit card numbers, personal information and other information that could be damaging to a person or a company. When they obtain this information, hackers will use the information to do damage to other such as send a virus using the usernames and passwords captured. However, in this project the system is built for the purpose of monitoring network traffic. Sniffalyzer is targeted to be implemented in a Local Area Network (LAN) environment. Its main function is to monitor, identify and control network traffic in real time. It helps to improve network manageability and overcome network problems. Sniffalyzer can be effective as security measure for the network and shared resources. All packets passing throughout the network can be captured and analyzed and these help to secure the network.